2016
DOI: 10.1136/neurintsurg-2016-012309
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment for ruptured and unruptured vertebral artery dissecting aneurysms: a meta-analysis

Abstract: Both internal trapping and stent-assisted coiling are technically feasible for ruptured vertebral artery dissecting aneurysms, with high rates of good long-term neurologic outcomes and low recurrence and mortality rates. For unruptured aneurysms, conservative treatment is recommended. When a posterior inferior cerebellar artery (PICA) origin is involved, bypass surgery or vertebral artery-to-PICA stent placement plus coil embolization should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…In a meta-analysis comparing deconstructive with reconstructive surgery for vertebral dissecting aneurysms, endovascular reconstructive surgery was as effective as deconstructive surgery, and also had a lower periprocedural morbidity 2. Another meta-analysis study comparing stent-assisted coiling with trapping showed that long-term outcomes and morbidity were similar 1. Vessel remodeling and reconstruction with flow diverters also has a distinct advantage for dissecting pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis comparing deconstructive with reconstructive surgery for vertebral dissecting aneurysms, endovascular reconstructive surgery was as effective as deconstructive surgery, and also had a lower periprocedural morbidity 2. Another meta-analysis study comparing stent-assisted coiling with trapping showed that long-term outcomes and morbidity were similar 1. Vessel remodeling and reconstruction with flow diverters also has a distinct advantage for dissecting pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of re-rupture of these aneurysms is high and treatment usually involves sacrifice of the parent vessel 1. With the advent of modern endovascular therapy, including stents and flow diverters, reconstructive interventions have been favored in many institutions for the treatment of intracranial vertebral artery dissecting pseudoaneurysms 2.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The rates of long-term occlusion, recurrence, and perioperative mortality are similar between deconstructive and reconstructive techniques in the treatment of VADAs. [57] However, aneurysm recanalization secondary to coil compaction and growth of the aneurysm sac remains a major shortcoming of reconstructive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4 Small unruptured dissecting aneurysms typically have a benign course, and conservative measures are often advocated, such as anticoagulation or antiplatelet therapy. 5 However, once ruptured, vertebrobasilar aneurysms carry a grim prognosis. The mortality rate is about 50%, and recurrent hemorrhage occurs in 24% to 70% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations can be diverse, and presentation may vary from acute onset headache, hydrocephalus, altered consciousness in the case of ruptured aneurysms, or cranial neuropathies or Horner's sign caused by mass effect of the lesion. 1,2,4,5 The distal vertebral artery segment (V4) is especially troublesome considering the presence of side arterial branches such as the posterior inferior cerebellar artery (PICA), the anterior spinal artery, and the posterior spinal arteries. The V4 segment represents the transition between the intracranial and extracranial segments that can be affected with extreme motion at the craniovertebral junction and also vulnerable to direct trauma against the foramen magnum.…”
mentioning
confidence: 99%